(untitled) (International Journal of Biology and Chemistry, 2015)
Thermo gravimetric study of coal in the presence of polymers showed that availability of high asphalt-resinous components – asphaltenes and resins benzene within the temperature of 360 – 443 С in the content was reduced. The optimum catalytics of coal hydrogenation is the compositions on the basis of Pd / C, at which there was the greatest absorption of hydrogen and Co / C, where the hydrogenation rate was maximum.